ESG Practice of Domestic Listed Companies - Song, Yina (International Journal of Global Economics and Management, 2024)
This article conducts in-depth research on the uniformity of the ESG (Environmental, Social, and Governance) information disclosure framework. The article points out that in order to ensure horizontal comparability of ESG information, a standardized disclosure framework similar to financial information must be implemented. The article emphasizes the importance of establishing a unified disclosure framework by analyzing the current situation of ESG information disclosure both domestically and internationally, especially the relevant laws, regulations, and guidelines in Europe and America. At the same time, the article also points out the problems in the ESG development of listed companies in China, including incomplete regulations, inconsistent disclosure frameworks, and insufficient information comparability. Based on these analyses, this article proposes suggestions for constructing a unified ESG disclosure framework in China to promote effective comparison and evaluation of ESG information among enterprises.